Exploring the Local Grammar of Evaluation: The Case of Adjectival Patterns in American and Italian Judicial Discourse - Pontrandolfo, Gianluca; Goźdź-Roszkowski, Stanisław (Research in Language, 2014)
Based on a 2-million word bilingual comparable corpus of American and Italian judgments, this paper tests the applicability of a local grammar to study evaluative phraseology in judicial discourse in English and Italian. In particular, the study compares the use of two patterns: v-link + ADJ + that pattern / copula + ADJ + che and v-link + ADJ + to-infinitive pattern / copula + ADJ + verbo all’infinito in the disciplinary genre of criminal judgments delivered by the US Supreme Court and the Italian Corte Suprema di Cassazione. It is argued that these two patterns represent a viable and efficient diagnostic tool for retrieving instances of evaluative language and they represent an ideal starting point and a relevant unit of analysis for a cross-language analysis of evaluation in domainrestricted specialised discourse. Further, the findings provided shed light on important interactions occurring among major interactants involved in the judicial discourse.